PENGUATAN USAHA MELALUI APLIKASI TEKNOLOGI TEPAT GUNA BAGI KELOMPOK PENGRAJIN TEMPE - Sunyoto, '; Sujiantoro, Hb.; Yoserizal, Yosta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
Tempe is one of food has been the most populist and suitable for all levels of society. On the other hand, many entrepreneurs of tempe in their business activities have not experienced significant development even though the business has been done for many years. It is because the lack of knowledge about business management, marketing management, and production support equipment is still conventional or manually by using a hand. Therefore, with an interactive-applicative method approach that involves participants as actively as possible, the team and partners solved the problem by providing training and mentoring and group-based strengthening support. With these methods, the implementation of the program activities can run well in accordance with the targets that have been planned. Indicators of success of the activity program can be seen the change of craftsmen after implemented, which are: (a) worker ethic of work increased, (b) productivity of craftsmen increased, (c) knowledge management business increased, where artisans can separate personal money with money, cash flow in and out and more discipline on business time. (d) The quality of tempe is better and hygienic, longer durability and broader marketing scope; (e) its waste can be used as goat feed (f) Forming a group cooperative of entrepreneurs of tempe that can strengthen business sustainability. In general, the entrepreneurs’ sales rate has increased by 9.5% from the previous.